(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The article generalizes the main methods and tools of the modern world policy of natural monopolies regulation. The essence, causes of appearance and sphere of activity of natural monopolies are determined. The basic principles of regulation of energy markets, the subjects of which are enterprises of natural monopolies, are formed: separation of managerial functions, non-discriminatory access to networks, transparency and publicity, independence of the regulatory body and the prohibition of cross-subsidization. The factors, taken into account by European Commission in the regulation of enterprises-monopolists are noted. The main approaches used by European countries in regulatory bodies creation for natural monopolies are considered. The analysis of regulatory changes of Ukrainian energy policy in the following areas was made: creation of adequate legal and regulatory framework that meets international requirements; options for the restructuring of the oil and gas complex and efficient energy market formation. The main disadvantages of demonopolization models of Ukrainian energy sector proposed by the Ministry of Energy and Coal Industry of Ukraine and Naftogaz of Ukraine are considered. The reasons for the competition lack in the retail segment, as well as the limited competition in the wholesale segment of the energy market were determined. The mechanism of regulated wholesale price for natural gas forming and the methodology for calculating the tariff for natural gas distribution are shown. The directions of improvement of the regulatory policy of Ukrainian energy sector are proposed.